Lectotypification of Areca dicksonii Roxburgh (Arecaceae) - Mane, Rohit N.; Lekhak, Manoj M.; Yadav, Shrirang R. (Phytotaxa, 2019)
A lectotype is designated for Areca dicksonii, the basionym of Pinanga dicksonii, which is the currently accepted name.